2018
DOI: 10.1016/j.bbi.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone potentiates DFP-induced neuroinflammation and affects high-order diffusion imaging in a rat model of Gulf War Illness

Abstract: Veterans of the 1991 Gulf War were potentially exposed to a variety of toxic chemicals, including sarin nerve agent and pesticides, which have been suspected to be involved in the development of Gulf War Illness (GWI). Several of these exposures cause a neuroinflammatory response in mice, which may serve as a basis for the sickness behavior-like symptoms seen in veterans with GWI. Furthermore, conditions mimicking the physiological stress experienced during the war can exacerbate this effect. While neuroinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 22 publications
2
61
0
Order By: Relevance
“…While both astroglia and microglia can release CCL2, in conditions with an active immune component and an absence of obvious neuronal damage, astroglia appears to be the major producers of CCL2 65 . Our current study shows that CCL2 levels are chronically elevated in GWI compared to the control which is consistent with findings of increased mRNA of this protein in another mouse model of GWI that was exposed to an organophosphate pesticide 54 . The release of CCL2 helps recruit macrophage/microglia to the damaged area and attracts CCR2 expressing monocytes from the periphery in response to injury or chemical exposure 66 , 67 , contributing to inflammation via CCR2 activation through NFκB and STAT3 pathways 40 , 41 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While both astroglia and microglia can release CCL2, in conditions with an active immune component and an absence of obvious neuronal damage, astroglia appears to be the major producers of CCL2 65 . Our current study shows that CCL2 levels are chronically elevated in GWI compared to the control which is consistent with findings of increased mRNA of this protein in another mouse model of GWI that was exposed to an organophosphate pesticide 54 . The release of CCL2 helps recruit macrophage/microglia to the damaged area and attracts CCR2 expressing monocytes from the periphery in response to injury or chemical exposure 66 , 67 , contributing to inflammation via CCR2 activation through NFκB and STAT3 pathways 40 , 41 .…”
Section: Discussionsupporting
confidence: 91%
“…Memory impairment is one of the major complaints among veterans with GWI, and a recent meta-analysis comparing results of neuropsychological functioning in veterans with GWI across 14 studies has shown that veterans with GWI perform poorly on tasks relating to memory compared to controls 43 50 , possibly due to damage or inflammation in the hippocampal region 51 – 53 . Another recent study of neuropsychological functioning in military pesticide applicators from the Gulf War reported worse memory functioning in veterans exposed to pesticides and personal repellents during the war 54 . GWI animal studies have consistently shown chronic impairment in learning and memory in several rodent models of GWI 5 , 6 , 8 , 9 , 33 , 55 .…”
Section: Discussionmentioning
confidence: 96%
“…The overall objective of this study was to examine genome-wide epigenetic transcriptional modifications in the brain using an established mouse model of GWI [ 4 , 12 , 15 , 16 ]. Our previous research demonstrates that effects on neuroinflammatory pathways occur shortly after initial exposures.…”
Section: Introductionmentioning
confidence: 99%
“…These results were interpreted to suggest that off target (non-AchE) actions of OPs may be chiefly responsible for the observed changes in neuroinflammation (51). An additional study from the same group demonstrated that the observed neuroinflammatory effects of DFP+CORT in mice extend to rats as well and are accompanied by changes in microdiffusivity as detected by MRI (52). A recent study using RNAseq analysis found 32 genes that were differentially expressed in both the cortex and hippocampus of mice treated using the same DFP+CORT exposure regime mentioned above.…”
Section: Gw Toxins and Innate Immunitymentioning
confidence: 92%